2017
DOI: 10.1111/pbi.12846
|View full text |Cite
|
Sign up to set email alerts
|

Peanuts that keep aflatoxin at bay: a threshold that matters

Abstract: SummaryAflatoxin contamination in peanuts poses major challenges for vulnerable populations of sub‐Saharan Africa and South Asia. Developing peanut varieties to combat preharvest Aspergillus flavus infection and resulting aflatoxin contamination has thus far remained a major challenge, confounded by highly complex peanut–Aspergilli pathosystem. Our study reports achieving a high level of resistance in peanut by overexpressing (OE) antifungal plant defensins MsDef1 and MtDef4.2, and through host‐induced gene si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…Researchers from the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) have successfully applied this technique to peanuts. The question is whether this approach can also significantly reduce aflatoxin contamination in other crops and not just in groundnut [41]. …”
Section: Affordability Of Aflatoxin Mitigation Interventionsmentioning
confidence: 99%
“…Researchers from the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) have successfully applied this technique to peanuts. The question is whether this approach can also significantly reduce aflatoxin contamination in other crops and not just in groundnut [41]. …”
Section: Affordability Of Aflatoxin Mitigation Interventionsmentioning
confidence: 99%
“…Using multiple approaches in groundnut and maize have led to the identification of several moderate/low/high resistant lines for A. flavus infection and reduced aflatoxin contamination. These advances have facilitated the development of aflatoxinresistant transgenic groundnut (Sharma et al, 2018) and maize (Thakare et al, 2017); and it is expected that in the coming years, farmers may have access to superior and aflatoxin-resistant varieties. However, the release of transgenic cultivars is dependent on their acceptance by regulators in the target countries.…”
Section: Molecular Basis Of Aflatoxin Resistance Mechanisms Identificmentioning
confidence: 99%
“…In groundnut, very few reports on transgenic approaches are available substantiating the importance of host genes like PR and defensin (Xie et al, 2013;Arias et al, 2015). A study (Sharma et al, 2018) has shown that the overexpression of Medicago defensin genes-MsDef1 and MtDef4.2 reduced Aspergillus infection as well as AP in susceptible groundnut variety JL 24. The study also demonstrated a host-induced gene silencing (HIGS) mediated silencing of aflatoxin biosynthetic pathway regulatory genes aflM and aflP to inhibit AP.…”
Section: Transgenic Approaches For Resistance To a Flavus Infection mentioning
confidence: 99%
“…In such conditions, genetic transformation presents great potential in groundnut improvement to utilize genes from other species [44,69,140,141]. Likewise, the difficulties of plant regeneration by tissue culture techniques and selection of transgenic events [141][142][143] are being overcome by recent advances in groundnut transformation process [144]. To date, at least a dozen of successful groundnut transformations have been reported in the literature [68].…”
Section: Modern Approaches Technologies and Tools To Benefit Choicementioning
confidence: 99%